Dietary Lipids Affect the Onset of Hibernation in the Garden Dormouse (Eliomys quercinus): Implications for Cardiac Function - Giroud, Sylvain; Stalder, Gabrielle; Gerritsmann, Hanno; Kübber-Heiss, Anna; Kwak, Jae; Arnold, Walter; Ruf, Thomas (Frontiers in Physiology, 2018)
Dietary lipids strongly influence patterns of hibernation in herbivores. Increased dietary uptake of n-6 polyunsaturated fatty acids (PUFA), particularly of linoleic acid (LA, C18:2 n-6), enables animals to reach lower body temperatures (Tb), lengthens torpor bout duration, and results in lower energy expenditure during hibernation. Conversely, dietary n-3 PUFA impacts negatively on hibernation performance. PUFA in surrounding phospholipids (PL) presumably modulate the temperature-dependent activity of the sarcoplasmic reticulum (SR) Ca2+ ATPase 2 (SERCA2) and thus determine the threshold Tb still allowing proper heart function during torpor. We tested the effect of diets enriched with 10% of either corn oil (‘CO’, high n-6 PUFA, e.g. LA) or menhaden oil (‘MO’, long-chain n-3 PUFA, e.g. docosahexaenoic acid (DHA)) on hibernation performance and SERCA2 activity levels during torpor in garden dormice, an insectivorous, fat-storing hibernator. Prior to hibernation, individuals fed the MO diet showed an almost 9-times higher DHA levels and 30% lower LA proportions in white adipose tissue (WAT), reflecting the fatty acid composition of SR membranes, compared to CO-diet fed animals. When fed the MO diet, dormice significantly delayed their mean onset of hibernation by almost four days (range 0-12 days), compared with CO-diet fed animals. Hibernation onset correlated positively with WAT-DHA levels and negatively with WAT-LA proportions prior to hibernation. Subsequently, hibernating patterns were similar between the two dietary groups, despite a significant difference in WAT-LA but not in WAT-DHA levels in mid-winter. SR-PL fatty acid composition and SERCA2 activity were identical in torpid individuals from the two dietary groups in mid-winter. In line with our previous findings on Syrian hamsters, a granivorous, food-storing hibernator, SERCA2 activity correlated positively with LA and negatively with DHA levels of SR-PL in torpid dormice, although SERCA2 activity was about three-times higher in garden dormice than in Syrian hamsters at similar PL-DHA proportions. Similarly, minimal Tb during torpor decreased as SERCA2 activity increased. We conclude that (1) fatty acid composition of SR membranes modulates cardiac SERCA2 activity, hence determining the minimum Tb tolerated by hibernators, and (2) high DHA levels prevent hibernators from entering into torpor, but the critical levels differ substantially between species.